Understanding Student Sentiment Towards Informatics Engineering: Strategies to Attract High School and Vocational Graduates - Rahmat Taufik R. L. Bau; Hermila A; Mukhlisulfatih Latief (Teknika, 2025)
Higher education plays a crucial role in shaping the future of the younger generation, and in the ever-evolving digital era, technology has become an integral part of the education process. Amid the ongoing digital transformation, students’ interest in the Informatics Engineering major is increasing; however, challenges remain in attracting high school (SMA) and vocational school (SMK) students to pursue this field. This research aims to provide a deeper understanding of students' sentiments toward the Informatics Engineering major and to formulate an effective promotional strategy to encourage high school and vocational school graduates to choose this path. To achieve these objectives, the research employs the TextBlob classification method, a natural language processing tool that assigns sentiment polarity scores (positive, neutral, or negative) to textual data. Sentiment analysis was conducted on responses collected through questionnaires, involving number of high school and vocational school students. The results of the sentiment analysis for high school (SMA) students reveal that out of 209 data points, 93 tweets (44.5%) were categorized as positive sentiment, citing career prospects and academic opportunities as key motivators. In contrast, For vocational school (SMK) students, among 135 data points analyzed, 50 tweets (37.0%) were categorized as positive sentiment, prioritizing practical skills and industry readiness. Based on the findings, the study formulates targeted promotional strategies. For SMA students, the focus should be on showcasing career prospects, technical skill development, and success stories in the tech industry. For SMK students, the promotion should emphasize practical, hands-on skills, industry partnerships, and job-readiness. This research provides recommendations for tailored promotional approaches to enhance students’ awareness and interest in Informatics Engineering, thereby encouraging greater enrollment in the field.